Prevalence of obsessive-Compulsive symptoms and the level of fear due to COVID-19 pandemic among the undergraduate medical students in a tertiary care unit in Southern India - Aditi Arora; Alankrithi Chauhan; Shivani Sunil Dhonge; Nikita Pandey; Avani Dinesh; OCS FEAR COVID TEAM (Wolters Kluwer Medknow Publications, 2022)
Background: The emergence of COVID-19 and its consequences is causing widespread fears, anxiety, and worries. To overcome the transmission of COVID-19, people resorted to compulsive behaviors. Objectives: The objectives of this study were to assess the prevalence of obsessive-compulsive symptoms (OCSs) due to COVID-19 pandemic, the prevalence of level of fear due to COVID-19 pandemic, and to assess the factors associated with OCSs due to COVID-19 pandemic among the undergraduate medical students of in tertiary unit in Southern India. Methods: The cross-sectional study was conducted in 250 undergraduate medical students (both MBBS and BDS, from 1st to 4th year) in the institute. Students who had consented in the study were included as study participants. The Yale-Brown Obsessive-Compulsive Scale and Fear of COVID-19 Scale (FCV-19 S) were used in assessing OCSs and the level of fear due to COVID-19. Chi-square test and multiple logistic regression were used to compute the factors associated with OCS. Results: The mean age of the respondents was 21 ± 1.313 years. The prevalence of OCS in undergraduate medical students was 36 (14.4%), and the level of FCV-19 was 107 (42.8%). Male students (17.8%, 44.2%) had higher OCSs and levels of fear as compared to female students (13.6%, 42.4%). Students with FCV-19 were three (adjusted odds ratio-3.418, 95% confidence interval-1.596, 7.319) times more likely to manifest OCSs while factors such as age, gender, and course were not significantly associated with OCS. Conclusion: Psychological counseling for undergraduate students should be pivotal, especially during pandemics and outbreaks.